2018
DOI: 10.14740/jocmr3236w
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection and Headache: A Matched Case-Control Study in a Public Hospital in Durango City, Mexico

Abstract: BackgroundToxoplasma gondii (T. gondii) can disseminate to brain in infected hosts. Little is known about the magnitude of the association between this infection and headache. Therefore, we sought to determine the association of T. gondii seropositivity and headache in patients attending neurological consultations in a public hospital in Durango City, Mexico.MethodsThrough an age- and gender-matched case-control study, 105 patients suffering from headache and 105 subjects without headache were examined for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…A study of recurrent headaches in pediatric neurology patients found that 11% were positive for chronic T. gondii infection, and the majority of these patients had headaches most often in the frontal region [ 135 ]. A more recent study found that recurrent headaches were only statistically correlated with T. gondii on the basis of serointensity but were not correlated with seropositivity [ 136 ]. An earlier study found statistical significance between chronic T. gondii infection and migraine, describing 44% of patients experiencing migraine being positive for chronic T. gondii infection versus only 26% in healthy control subjects [ 134 ].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…A study of recurrent headaches in pediatric neurology patients found that 11% were positive for chronic T. gondii infection, and the majority of these patients had headaches most often in the frontal region [ 135 ]. A more recent study found that recurrent headaches were only statistically correlated with T. gondii on the basis of serointensity but were not correlated with seropositivity [ 136 ]. An earlier study found statistical significance between chronic T. gondii infection and migraine, describing 44% of patients experiencing migraine being positive for chronic T. gondii infection versus only 26% in healthy control subjects [ 134 ].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…In addition, in a study by Koseoglu et al, it was reported that Toxoplasma gondii was associated with migraine and was concluded that this infection may cause a neuroinflammatory process in the brain, thereby triggering migraine [8]. In a study comparing 105 patients with headache and 105 non-headache subjects, it was reported that the case and control group were similar in terms of Toxoplasma seropositivity [15]; however, interestingly, the level of IgG for Toxoplasma gondii was suggested to be associated with headache -even when the patient group included other types of headaches in addition to migraine (39 patients with migraine in the 105 subjects). Since this infection is very prevalent among humans, has a chronic characteristic in an estimated 30% of individuals [16] and the fact that the infection may persist in the brain [17], have supported the rationale of studies aiming to determine a relationship (if any) between headache and Toxoplasma gondii infection.…”
Section: Discussionmentioning
confidence: 99%
“…The parasite was also found to be associated with development of a number of other mental health disturbances, such as depression [131], suicide attempts [27,132,133], anxiety disorder [131,134,135], autism [136], schizophrenia [135,137,138], and headaches [139][140][141]. It should be emphasized that several drugs used in treatment of schizophrenia or other neuropsychiatric diseases inhibited replication of T. gondii tachyzoites [142].…”
Section: B Perfectionism In Patients With Some Neuropsychiatric Disor...mentioning
confidence: 99%